Pemberian Dolomit Pada Kultur Daphnia spp. Sistem Daily Feeding Pada Populasi Daphnia spp. dan Kestabilan Kualitas Air [Dolomite Added At Culture Of Daphnia spp. Daily Feeding System At Daphnia spp. Population and Water Quality Stability]. - A. Shofy Mubarak; Laksmi Sulmartiwi; Diah Trie Ridyaning Tias (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
Abstract Daphnia spp. was potential source of live feed to be developed for larvae of freshwater fish. One of maximize culture technology was daily feeding system with rice bran solution. This system able to increase Daphnia spp. population. The problem of daily feeding culture technology was water quality stability, such as high pH fluctuation and high ammonia concentration. Water pH stability and decrease of ammonia concentration could be increased by dolomite added which function as stabilize pH buffer. The aim of this research found out the dolomite dose and culture period that able to increase population and stabilize of water quality. Experimental design was Completely Random Design with 4 replicates those were A control (0 mg/l), B (50 mg/l), C (100 mg/l), D (150 mg/l), E (200 mg/l) and F (250 mg/l). Parameter that measured were Daphnia spp. population and water quality, such as temperature, pH, ammonia, dissolve oxygen and alkalinity. The data were examined using ANAVA(Analysis of Variance) to know treatment effect and be continued by Duncan Multiple Range with trust of degree 0,05. for water stability using descriptif methode. Result of analysis showed that high population for all treatment were held on 6th, 7th and 8th day with the highest Daphnia spp. population was held on 8th day by F treatment (250 mg/l) were 9900 Daphnia spp./l. Water quality data showed different between each treatment.